THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF THE SEVENTH-GRADE STUDENTS OF SMPN 2 KUTA UTARA IN ACADEMIC YEAR 2020/ 2021 - Ni Komang Ayu Ningsih; Luh Ketut Sri Widhiasih; Nengah Dwi Handayani (Academic Journal on English Studies (AJOES), 2021)
This study was designed in the form of ex-post facto research. It was aimed at finding out the correlation between vocabulary mastery and reading comprehension of the seventh-grade students of SMPN 2 Kuta Utara in academic year 2020/2021”. There were 68 seventh-grade students of SMPN 2 Kuta Utara in academic year 2020/2021 which was regarded as the samples under study. They were taken by using cluster random sampling technique with lottery system. Besides, the present study was conducted with two instruments those were short answer tasks that was used to assess reading comprehension and cloze tasks for vocabulary mastery test. Moreover, to find out the correlation between two variables, the obtained data were analysed by using Product Moment’s formula and analysed by using the Statistical Package for Social Science (SPSS) 19. The results of the data analysis showed that there was a significant, and positive correlation between vocabulary mastery and reading comprehension of the seventh-grade students of SMP N 2 Kuta Utara in academic year 2020/2021.